The Impact of TQM Factors on Employees Job Satisfaction - Faiz, Akashah (2010)
The key element to a successfully business continuance is the implementation of Total Quality Management but however if not properly implemented or used it can lead to a failure. The theory behind Total Quality Management is sound so the problems that can be generated from the usage and implementation must come from another important source. This source is the leadership and employees of that particular organization. The leadership or management of an organization and the employees can greatly impact the final outcome of a Total Quality Management implementation. Just how Total Quality Management can give impact on organizational leadership and employees on their job satisfaction is a topic that is often not considered well until a Total Quality Management project and issues begin to arise. From the literature, five antecedents of employee job satisfaction are identified. The variables measured are "employee participation", "teamwork, "recognition and rewards", "organizational culture" and "education and training". This research seeks to investigate the employees' perception on the Total Quality Management factors and its impact on job satisfaction in a manufacturing facility. A total of 120 questionnaires were distributed, 98 questionnaires were returned and useable representing 82 percent response rate. The Pearson correlations test results showed that "educational and training" is the top influential factors in determining employees' job satisfaction. On the other hand, "employee participation" is the second significantly that influenced job satisfaction followed by "teamwork and "organizational culture". Lastly, "recognition and rewards" suggests that employees need to be monitored in order to have a better job. The findings could prescribe potential implications for top management to review their TQM programs. Managers must, therefore, consider these factors in all TQM initiatives.